Implementation of Accurate Online Accounting System in the Management of Daily Financial Reports at PT. Mega Vastech Pratama - Pascalya, Yesaya; Pravitasari, Endyastuti (SJEE (Scientific Journals of Economic Education), 2026)
This study aims to examine the implementation of the Accurate Online accounting system in managing daily financial reports at PT. Mega Vastech Pratama. The methods used in this internship include direct observation of financial workflows, work practices as finance staff, and guidance from field supervisors. Students are directly involved in fund withdrawal activities, recording incoming and outgoing cash flows, recapitulating daily transactions, and journaling transactions into the Accurate Online system. The results of the activities indicate that the use of Accurate Online can improve the orderliness of financial records, minimize the risk of recording errors, and accelerate the preparation of daily financial reports. In addition, this system helps companies monitor cash flows more effectively and transparently. These findings indicate that the use of digital-based accounting systems is very important for companies with high transaction activity. The implication of this activity is that the implementation of Accurate Online can be an effective solution for companies in improving the efficiency, accuracy, and quality of daily financial report management, as well as providing relevant practical experience for students in facing the world of work.